The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1038/s41586-020-2170-7
|View full text |Cite
|
Sign up to set email alerts
|

Universal quantum logic in hot silicon qubits

Abstract: Quantum computation requires many qubits that can be coherently controlled and coupled to each other [1]. Qubits that are defined using lithographic techniques are often argued to be promising platforms for scalability, since they can be implemented using semiconductor fabrication technology [2][3][4][5]. However, leading solidstate approaches function only at temperatures below 100 mK, where cooling power is extremely limited, and this severely impacts the perspective for practical quantum computation. Recent… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
250
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 282 publications
(265 citation statements)
references
References 44 publications
(65 reference statements)
14
250
0
1
Order By: Relevance
“…[ 6,7 ] Second, charge noise hinders spin‐cavity coupling through the charge degree of freedom, [ 9–11 ] posing a challenge for designing efficient long‐range interconnects between qubits. Finally, for two‐qubit gates where the coupling between two electron spin qubits is achieved via the exchange interaction with strength J , [ 3,12–18 ] the charge noise results in J fluctuations during the two‐qubit gate operation limiting the overall gate fidelity. [ 3,15,16,19 ]…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…[ 6,7 ] Second, charge noise hinders spin‐cavity coupling through the charge degree of freedom, [ 9–11 ] posing a challenge for designing efficient long‐range interconnects between qubits. Finally, for two‐qubit gates where the coupling between two electron spin qubits is achieved via the exchange interaction with strength J , [ 3,12–18 ] the charge noise results in J fluctuations during the two‐qubit gate operation limiting the overall gate fidelity. [ 3,15,16,19 ]…”
Section: Figurementioning
confidence: 99%
“…The σ ε values are typically measured using a double quantum dot system, where the fluctuations in the detuning energy ϵ between the two dots result in observable dephasing of coherent exchange oscillations. [ 3,15,17,39–44 ] Due to the 1/ f nature of charge noise, the integrated charge noise σ ε is dominated by the low‐frequency noise components. Therefore, it is desirable to keep the total measurement time T M as short as possible because it is T M that determines the low‐frequency limit of the noise bandwidth f low = 1/ T M .…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…In this work, the focus is on the design of a controller operating at 3 K because of the higher available cooling power. This does not restrict a future co-integration with qubits at the same temperature as the electronics since "hot" qubits operating at temperatures above 1 K have recently been demonstrated and are likely to evolve further in the next few years [20], [21].…”
Section: Introductionmentioning
confidence: 99%
“…The co-integration of the qubits and the peripheral electronics on the same substrate, the so-called quantum-integrated circuits, would be the following step in the quantum computing roadmap. Recent studies have already demonstrated silicon qubit operating above 1 K [4], [5]. With further engineering of qubits, it might be possible to increase the operating temperature of qubits to ~4.2 K, therefore having the whole system operating at that temperature.…”
Section: Introductionmentioning
confidence: 99%